Bonding and Spectral Character of Cr Doped Cdte, Cdse and Cds Nano-Clusters. (December 2015) - Xu, Shuhong; Du, Jinhua; Wang, Chunlei; Wang, Zhuyuan; Cui, Yiping
The geometrical structures, bonding characteristics, Raman spectra, and molecular orbitals of hexagonal and tetrahedral Cr-doped CdX molecules have been investigated using density functional theory calculations at the B3LYP/LANL2DZ level. The structures of Cr-doped CdX molecules had obvious distortions compared with pure CdX clusters, especially CdCr2 Se3 and CdCr2 S3 clusters. The Mulliken charges of Cr atoms were negative and were lower than those of Cd atoms in the corresponding structures. Raman spectra showed that there was the vibration of the Cr–Cr bond in Cr-doped CdX molecules. Wiberg bond indices (WBI) values show that there were Cr–Cr bonds in some clusters. WBI values have also revealed that bonds between Cr and Te, Se, S were stronger than those between Cd and X atoms. Finally, molecular orbital observations indicate that the transitions in doped structures were from d orbital to d orbital, which is different from undoped structures.